Jumlah Kepala Sekolah Dan Guru Menurut Kelompok Umur Provinsi Sumatera Barat, Jawa Timur, Kalimantan Selatan, Sulawesi Selatan Tahun 2023/2024 - Rosyani, Perani; Sentia, Melsa; Hamzah, Amri; Idris Prasetya, Galuh; Fariz, Muhammad (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
The distribution of principals and teachers in the provinces of West Sumatra, East Java, South Kalimantan and South Sulawesi affects the development of education in these four provinces. The uneven distribution and different generations of teaching staff as well as the lack of knowledge of senior teachers who understand the latest technology cause problems in the teaching and learning process. These problems cause variations in the quality of teaching between schools in one region and another. Students in certain areas may have a more limited learning experience than students in other areas where teachers are younger and experienced with technology. In addition, the lack of demographic data-based succession planning can lead to gaps in teaching methods between generations which can lead to a decline in the quality of education. Therefore, researchers are interested in conducting research related to the number of principals and teachers by age group in four provinces, namely in the provinces of West Sumatra, East Java, South Kalimantan and South Sulawesi. This journal uses descriptive quantitative research methods where researchers analyze data on teaching staff from Dapodik 2023/2024 using the literature review method, namely by collecting sources such as articles, journals and books related to the topic under study and then analyzing them. The goal is to optimize educational resource planning that can overcome the generation gap in the teaching force and improve the quality of education through intergenerational knowledge transfer. The solution to the above problem is to implement a cross-generational mentoring program where senior teachers share their teaching experience while junior teachers help with technology adaptation supported by continuous technology training and continuous competency development programs through digital certification and training in modern teaching methods, to ensure equitable quality of education throughout the region. Results show the highest concentration in the 36-40 years age group. The findings provide a basis for strategic planning of education human resource development and data-driven policy recommendations.